2021
DOI: 10.1093/jscr/rjab203
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approach in radio distal end fractures, three different types of incisions

Abstract: Two techniques are described to treat distal radius fractures: conventional (Henry approach) and minimally invasive plate osteosynthesis. The latter technique has been described by different authors such as Imatani et al. and Zenke et al. This was a descriptive retrospective study, analyzing 26 adult patients with unstable distal radius fracture, extra-articular type A or partially intra-articular type B according to AO. The approaches used were: (i) single longitudinal palmar incision; (ii) dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, our study used general anesthesia. Romero Prieto et al [ 12 ] previously reported using general anesthesia to treat distal radius fractures. General anesthesia may be suitable for patients with anxiety, long surgery duration, or contraindications for regional anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study used general anesthesia. Romero Prieto et al [ 12 ] previously reported using general anesthesia to treat distal radius fractures. General anesthesia may be suitable for patients with anxiety, long surgery duration, or contraindications for regional anesthesia.…”
Section: Discussionmentioning
confidence: 99%